A 3D genome atlas of human tonsil and the role of loop extrusion in B cell somatic hypermutation - Yubao Cheng; Jianshu Wang; Yuan Zhang; Anurupa Devi Yadavalli; Miao Liu; Shengyan Jin; Grace Buddle; Ann Haberman; David G. Schatz; Siyuan Wang (Science, 2026)
B cell maturation within the germinal center tissue microenvironment involves immunoglobulin gene diversification by somatic hypermutation (SHM). How three-dimensional (3D) genome architecture influences SHM is not fully understood. We leveraged sequencing-based and image-based 3D genomics and transcriptomics to map single-cell 3D genome organization and gene expression across cell types and states in human tonsils and in B cell lymphoma cell lines. These analyses revealed trajectories of compartment, looping, and nuclear position changes during the B cell immune response and activation of SHM. Targeted protein degradation of cohesin component RAD21 revealed its contribution to enabling SHM. Our results provide a single-cell 3D genome atlas of human tonsil cells and outline the links between the chromatin loop extrusion machinery and SHM.